METHODS OF TEACHING THE RUSSIAN LANGUAGE TO FOREIGN STUDENTS - Abdualieva Durdona Rustamovna (Journals Park Publishing, 2023)
Each country has its own unique methodology for teaching foreign language, which has developed over years of practice. It takes into account many factors that can affect language learning, such as the geopolitical position of the country, the characteristics of the learning conditions, the national mentality, the proximity of the Russian language to the native language and the practical value of the language being studied.
Keywords: speech activity, language proficiency, connections, analogies, anticipation, addition, well-known words, idiomatic expressions, constructions, unfamiliar material.